Seaweeds’ neuroprotective potential set in vitro on a human cellular stress model - Silva, Joana (2020)
Neurodegenerative diseases, such as Parkinson’s disease, represent a biggest challenge for medicine, imposing high social and economic impacts. As a result, it is of utmost importance to develop new therapeutic strategies. The present work evaluated the neuroprotective potential of seaweeds extracts on an in vitro dopamine (DA)-induced neurotoxicity cellular model. The neuroprotective effects on SH-SY5Y cells’ viability were estimated by the MTT assay. Changes in mitochondrial membrane potential (MMP), caspase-3 activity, and hydrogen peroxide (H2O2) production were determined. DA (30–3000 μM; 24 h) treatment decreased SH-SY5Y cells’ viability in concentration and time-dependent manner, increasing the H2O2 production, MMP depolarization, and caspase-3 activity. On the other hand, DA (1000 μM; 24 h) toxicity was reduced (10–15%) with Sargassum muticum and Codium tomentosum extracts (1000 μg/mL; 24 h). The highest neuroprotective activity was exhibited by a methanolic extract obtained from Saccorhiza polyschides, which completely blunted DA effects. Results show that the marine seaweed S. polyschides contain substances with high neuroprotective potential against the toxicity induced by DA, exhibiting anti-apoptotic effects associated with both mitochondrial protection and caspase-3 inhibition. S. polyschides reveals, therefore, to be an excellent source of bioactive molecules, for new drugs development aiming PD therapeutics.